Design and Structural Analysis of a Maca Freeze-Dryer for the Peruvian High Andean Zones Using VDI 2221 - Quispe Aguirre, Beyker Jesús (2024)
In recent decades, the interest and demand for maca (Lepidium meyenii) have grown worldwide, establishing the tuber as one of Peru's flagship products, so adding value to it without losing its nutritional properties is a viable option to further increase its production and sale. Therefore, the most efficient process to consider is freeze-drying, which allows for preserving most of the organoleptic and nutritional properties of the food over time. The objective of this work is to design a compact and easy-to-use machine, which allows generating an added value to maca through freeze-drying. For this purpose, the VDI 2221 methodology was used, where a list of requirements was considered according to the structure of the freeze-dryer, a black box, and a white box, which led to making the morphological matrix from which the optimal 3D prototype was obtained. The result of this design showed that the machine provides 1 kg/batch of production and that the structure supported the size of the freeze dryer with a maximum deformation of 0.004491 mm, on the other hand, the part of the structure that supported the vacuum pump was prone to breakage. This research concludes that the use of the VDI 2221 methodology has the potential to structure the important functions and components for machine design, but another methodology is needed to help organize the processes systematically.